2018
DOI: 10.1016/j.bbalip.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of regulation of sphingosine kinase 1

Abstract: Within the last 3 decades, there has been intense study of bioactive sphingolipids and the enzymes which metabolize those lipids. One enzyme is the critical lipid kinase sphingosine kinase 1 (SK1), which produces the potent and pleiotropic signaling lipid, sphingosine 1-phosphate (S1P). SK1 and S1P have been implicated in a host of different diseases including cancer, chronic inflammation, and metabolic diseases. However, while there is ample knowledge about the importance of these molecules in the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 91 publications
0
24
0
Order By: Relevance
“…Another study localized L194, F197, and L198 within a hydrophobic patch on the surface of SphK1 and demonstrated that hSphK1-L194Q and hSphK1-F197A-L198Q did not bind to acidic liposomes in vitro and were not recruited to tubular membrane invaginations induced by cholesterol extraction in living cells [ 4 ]. Hence, this hydrophobic patch is regarded as essential for curvature-sensitive membrane binding of SphK1 [ 9 , 21 ]. We show here that the two hSphK1 mutants, hSphK1-L194Q-GFP and hSphK1-F197A-L198Q-GFP, did not visibly translocate to the plasma membrane in response to M 3 receptor activation in HEK-293 cells ( Figure 5 A–C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study localized L194, F197, and L198 within a hydrophobic patch on the surface of SphK1 and demonstrated that hSphK1-L194Q and hSphK1-F197A-L198Q did not bind to acidic liposomes in vitro and were not recruited to tubular membrane invaginations induced by cholesterol extraction in living cells [ 4 ]. Hence, this hydrophobic patch is regarded as essential for curvature-sensitive membrane binding of SphK1 [ 9 , 21 ]. We show here that the two hSphK1 mutants, hSphK1-L194Q-GFP and hSphK1-F197A-L198Q-GFP, did not visibly translocate to the plasma membrane in response to M 3 receptor activation in HEK-293 cells ( Figure 5 A–C).…”
Section: Resultsmentioning
confidence: 99%
“…There are two SphK isoforms, which are derived from different genes and differ in tissue expression, structure, subcellular localization, regulation, and function. SphK2 has been observed in the cytosol, ER, mitochondria, and nucleus, whereas SphK1 is mainly found in the cytosol and may translocate to the plasma membrane upon stimulation [ 7 , 8 , 9 , 10 ]. Thus, SphK1 seems to be poised to generate S1P for cellular export, and thereby trigger S1P-GPCR cross-activation, which is known as inside-out signaling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This extends our previous study connecting oncogenic K-Ras to SK1, and the current results suggest K-Ras regulates SK1 translation or protein stability. Of note, several micro RNA (miRNA) and long non-coding RNA (lncRNA) can negatively regulate SK1 translation 68 . Thus, oncogenic suppression of such miRNA and lncRNA could lead to increased SK1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation or inhibition of metabolic enzymes, particularly SPHK1 in RBC and deprivation of RBC content of S1P could be a potent therapeutic against malaria infection. A recent article by Pulkoski-Gross and Obeid ( 2018 ) describes SPHK1 regulation at different levels starting from transcription to post-translational modification through the use of long non-coding RNAs, micro RNAs, small interfering RNAs, and physiological and pharmacological stimuli. However, RBC being devoid of nucleus and genetic material, these methods of regulation seem ineffective.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%